Protocols for Assessing Transformation Rates of Nitrous Oxide in the Water Column - Bourbonnais, Annie; Frey, Claudia; Sun, Xin; Bristow, Laura A.; Jayakumar, Amal; Ostrom, Nathaniel E.; Casciotti, Karen L.; Ward, Bess B. (Frontiers in Marine Science, 2021)
Nitrous oxide (N2O) is a potent greenhouse gas and an ozone destroying substance. Yet, clear step-by-step protocols to measure N2O transformation rates in freshwater and marine environments are still lacking, challenging inter-comparability efforts. Here we present detailed protocols currently used by leading experts in the field to measure water-column N2O production and consumption rates in both marine and other aquatic environments. We present example 15N-tracer incubation experiments in marine environments as well as templates to calculate both N2O production and consumption rates. We discuss important considerations and recommendations regarding (1) precautions to prevent oxygen (O2) contamination during low-oxygen and anoxic incubations, (2) preferred bottles and stoppers, (3) procedures for 15N-tracer addition, and (4) the choice of a fixative. We finally discuss data reporting and archiving. We expect these protocols will make 15N-labeled N2O transformation rate measurements more accessible to the wider community and facilitate future inter-comparison between different laboratories.